Determinants of Risk Factors and HIV/AIDS Prevention Among Seafarers: A Narrative Review - Muhammad Noor; Irfansyah Baharuddin Pakki; Yadi Yadi (Mulawarman International Conference on Tropical Public Health, 2025)
Seafarers are a highly mobile maritime workforce vulnerable to risky sexual behaviors and limited access to HIV/AIDS testing and counseling. The dynamic port environment, combined with social and behavioral factors, heightens the risk of HIV transmission. Objective : to synthesize research findings on individual, social, and structural factors influencing HIV/AIDS prevention behaviors among seafarers in various ports in Indonesia and abroad. Research Methods/ Implementation Methods : A Narrative Review was conducted using PubMed, Google Scholar, and ScienceDirect databases for studies published from 2019 to 2025. Eligible studies included quantitative or qualitative research addressing risk factors, preventive behaviors, or access to HIV-related health services among seafarers. Studies focusing solely on technical shipping aspects were excluded. Twenty-six articles met the inclusion criteria and were analyzed descriptively Results : Risky behaviors among seafarers were shaped by individual (knowledge, attitude, condom use), social (peer support, influence of sex workers, docking duration, marital status), and structural factors (health service access, port policy, education). Condom use was the most dominant protective factor, while knowledge alone did not guarantee preventive behavior. Institutional and peer support promoted safe practices, but limited screening and counseling services at ports remained barriers. Cross-sector collaboration and free services supported better prevention outcomes Conclusion/Lesson Learned : Effective HIV/AIDS prevention among seafarers requires multidimensional interventions addressing behavioral, social, and policy aspects. Strengthening port health services, enhancing education, and expanding counseling and testing access are essential to reduce HIV risk in maritime populations